JARINGAN PEMASARAN TANDAN BUAH SEGAR (TBS) KELAPA SAWIT DI KECAMATAN SABAK AUH KABUPATEN SIAK - Kurnia Nursianti; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This study was conducted at Sabak Auh District Of Siak Regency. The purpose of this research is to know the characteristic of PERON which has production relation with oil palm farmer at Sabak Auh District Of Siak Regency. The focus of this research is the marketing chain of PERON and palm oil trading which illustrates the relationship between buying and selling TBS at Sabak Auh District Of Siak Regency. The technique of determining samples in a purposive sampling and set the number of samples as many as 9 people. The author uses qualitative descriptive method and Instrument data is observation, interview and documentation. Research conducted found there are some characteristics of PERON at Sabak Auh District Of Siak Regency namely as follows: Provide capital, PERON willing and always willing if there are people who want to open a business as Tauke and also small farmers, then the PERON will provide material assistance. Place / land, PERON at Kecamatan Sabak Auh generally run a business on community owned land rented for Rp 5,000,000-8.000.000 / month. Employment of PERON, All PERON at Sabak Auh District Of Siak Regency take the workforce from the community around PERON in order to reduce unemployment at Sabak Auh District Of Siak Regency. Work methods, Work methods defined by all PERON at Sabak Auh District Of Siak Regency That is starting from the selection of quality palm fruits, adjust the price with the quality of palm, and then bought with a price agreement set. In addition, the research also found there are several marketing chains of palm, which are as follows: Farmer-Tauke, Farmer-Factory, Tauke-PERON, Tauke-Factory. Furthermore, researchers also find some forms of competition PERON, which is as follows: Palm fruit sold to PERON by Tauke or the community has passed the price agreement in accordance with the agreement of both parties, and Ada apply by keeping buying palm with a price even if the price of palm oil is falling, providing assistance to farmers and Tauke in need, as well as maintaining good communication between farmers and Tauke palm Keywords: Marketing Network, Competition, PERON